2016
DOI: 10.4171/161-1/3
|View full text |Cite
|
Sign up to set email alerts
|

On Grothendieck’s construction of Teichmüller space

Abstract: Abstract. In his 1944 paper Veränderliche Riemannsche Flächen, Teichmüller defined a structure of complex manifold on the set of isomorphism classes of marked closed Riemann surfaces of genus g. The complex manifold he obtained is the space called today Teichmüller space. In the same paper, Teichmüller introduced the so-called universal Teichmüller curve -a space over Teichmüller space where the fiber above each point is a Riemann surface representing that point. In fact, Teichmüller proved the existence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…According to Courant [64, p. 178], "If today we are able to build on the work of Riemann, it is thanks to Klein." 3 In the book [45], Klein tried to explain some work of Riemann in ways he thought that Riemann did it. For example, the title of Chapter 19 of Part III of this book is On the moduli of Algebraic Equations.…”
Section: Klein's Booklet On Riemann's Work and The Methods Of Continuity To Prove The Uniformization Theorem By Klein And Poincarémentioning
confidence: 99%
“…According to Courant [64, p. 178], "If today we are able to build on the work of Riemann, it is thanks to Klein." 3 In the book [45], Klein tried to explain some work of Riemann in ways he thought that Riemann did it. For example, the title of Chapter 19 of Part III of this book is On the moduli of Algebraic Equations.…”
Section: Klein's Booklet On Riemann's Work and The Methods Of Continuity To Prove The Uniformization Theorem By Klein And Poincarémentioning
confidence: 99%
“…The notion of analytic continuation was known to Weierstrass before Riemann, and is present in unpublished papers he wrote in 1841 through 1842. 9 Riemann was aware of this concept when he wrote his thesis in 1851, but it is unlikely that he had access to Weierstrass' notes. 10 7 The sphere is, in Riemann's words: "die ganze unendliche Ebene A."…”
Section: Riemannmentioning
confidence: 99%
“…Pringsheim and Faber [198]. 9 These papers are reported on in [27]. Weyl, in [267] p. 1, also refers to an 1842 article by Weierstrass [247].…”
Section: Riemannmentioning
confidence: 99%
“…Taking infinite covers forces one to deal with schemes which are not of finite type. 3 Let us also note by the way that the notion of "tower" is dear to the twentieth century algebraic geometers, and several towers existed before Grothendieck introduced some very important ones. We shall review for instance the Postnikov tower in Section 3 of this paper, a tower which is also related to the actions of the absolute Galois group.…”
Section: Introductionmentioning
confidence: 99%
“…From the one-to-one correspondence between dessins d'enfants and covers of the Riemann sphere S 2 with ramification points at {0, 1, ∞}, we get an action of Γ Q on the algebraic fundamental group of S 2 − {0, 1, ∞}. But this fundamental group is the first level of the Teichmüller tower, since it is the fundamental group of the 3 In the paper [88], it is shown that infinite coverings, although no more algebraic, do convey essential arithmetic information. What is studied in that paper is a version of the "annular uniformization" of the thrice-punctured sphere that is developed in Strebel's book on quadratic differentials [78].…”
Section: Introductionmentioning
confidence: 99%